SPECIFIC ASPECTS OF ORGANIZING STATE CIVIL SERVICE IN LOCAL GOVERNMENT AUTHORITIES OF THE REPUBLIC OF KARAKALPAKSTAN - K.P.Seitniyazov (Antis Publisher, 2024)
The organization of civil service within local government authorities is critical for effective governance, particularly in the context of the Republic of Karakalpakstan. General Background: This study delves into the legal frameworks governing civil service in district and city administrations, emphasizing the unique characteristics that define the local governance landscape. Specific Background: Given the distinct socio-political context of Karakalpakstan, it is imperative to explore how local and foreign scholars perceive the efficacy and challenges of civil service organization. Knowledge Gap: Despite existing literature on civil service structures globally, there remains a paucity of research specifically addressing the nuances of civil service in Karakalpakstan's local government, creating a significant knowledge gap. Aims: This article aims to elucidate the legal foundations and operational frameworks of civil service in local authorities, while critically analyzing scholarly perspectives on its effectiveness. Results: The findings reveal that local governance in Karakalpakstan is shaped by a blend of national policies and regional practices, highlighting both achievements and areas needing reform. Novelty: This research contributes to the field by offering a comprehensive examination of civil service organization within a specific regional context, which has been largely overlooked in existing studies. Implications: The insights gleaned from this analysis can inform policymakers and practitioners, providing a foundation for enhancing the efficiency and accountability of civil service in Karakalpakstan's local governments, ultimately fostering better governance and public service delivery.